Kepemimpinan Lembaga Pendidikan Islam pada Pondok Pesantren - Ibrahim; Hasanudin (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2022)
Leadership is the most interesting side to be studied more intensively in management studies. The context of leadership is quite dynamic and continues to experience fundamental changes according to the context of the development of human life, including leadership in Islamic educational institutions. The basis of change always starts with a long process of changing the basic values of life in society, which at the next level changes their communication patterns, basic needs, and outlook on life. Changes in this area of life have an impact on organizational leadership in terms of developing a vision and mission statement, as well as taking steps to achieve organizational goals. As a result, the focus of this study is more on how the future of Islamic educational institutions will provide answers to the community in meeting their needs from a leadership standpoint. A qualitative study will provide an overview of the data behind what appears to be seen from ideas, ideas, and strategies in managing the management of educational institutions, which are urgent matters in changing the direction and achieving educational institution goals. According to the study's findings, based on the data, changes in leadership typologies are demands from changes in organizational management in achieving common goals. Therefore, changes in leadership typology will have an impact on the sustainability and quality of Islamic education in Indonesia in the future. Leaders of Islamic educational institutions are currently required to design organizational management that can move all elements and elements of strength towards organizational progress in responding to the challenges of change.